New phenylspirodrimane metabolites MBJ-0030, MBJ-0031, and MBJ-0032 isolated from the soil fungal strain Stachybotrys sp. f23793. Issue 8 (2nd August 2020) - Kawahara, Teppei; Itoh, Masashi; Izumikawa, Miho; Kagaya, Noritaka; Sakata, Noriaki; Tsuchida, Toshio; Shin-ya, Kazuo
ABSTRACT: Chemical screening of culture medium from the soil fungus Stachybotrys sp. resulted in the isolation of the three new phenylspirodrimanes MBJ-0030 (1 ), MBJ-0031 (2 ) and MBJ-0032 (3 ). Their structures were determined by detailed analysis of spectroscopic data. The absolute configurations of 1 –3 were determined by modified Mosher's and Marfey's methods. In addition, cytotoxic and antimicrobial evaluations of the compounds were conducted. GRAPHICAL ABSTRACT: uf0001 The structure of new phenylspirodrimane metabolites MBJ-0030, MBJ-0031, and MBJ-0032 isolated from the soil fungal strain Stachybotrys sp. f23793.